Lipid nanobilayers to host biological nanopores for DNA translocations - Göpfrich, Kerstin (Langmuir : the ACS journal of surfaces and colloids, 2013)
We characterize a recently introduced novel nanobilayer technique [Gornall, J. L., Mahendran, K. R., Pambos, O. J., Steinbock, L. J., Otto, O., Chimerel, C., Winterhalter, M., and Keyser, U. F. Simple reconstitution of protein pores in nano lipid bilayers. Nano Lett. 2011, 11 (8), 3334-3340] and its practical aspects for incorporating the biological nanopore α-hemolysin from Staphylococcus aureus and subsequent studies on the translocation of biomolecules under various conditions. This technique provides advantages over classical bilayer methods, especially the quick formation and extended stability of a bilayer. We have also developed a methodology to prepare a uniform quality of giant unilamellar vesicles (GUVs) in a reproducible way for producing nanobilayers. The process and the characteristics of the reconstitution of α-hemolysin in nanobilayers were examined by exploiting various important parameters, including pH, applied voltage, salt concentration, and number of nanopores. Protonation of α-hemolysin residues in the low pH region affects the translocation durations, which, in turn, changes the statistics of event types as a result of electrostatics and potentially the structural changes in DNA. When the pH and applied voltage were varied, it was possible to investigate and partly control the capture rates and type of translocation events through α-hemolysin nanopores. This study could be helpful to use the nanobilayer technique for further explorations, particularly owing to its advantages and technical ease compared to existing bilayer methods